Hubungan Father Involvement dengan Kontrol Diri Siswa Madrasah Tsanawiyah - Putri, Amanda Aulia; Zahri, Triave Nuzila; Taufik, Taufik; Sari, Azmatul Khairiah; Putra, Ade Herdian (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2025)
This study aims to describe and examine the relationship between father involvement and student self-control, based on the persistent issues of truancy and low self-regulation among students. The research employed a quantitative method with a descriptive correlational approach. The study population consisted of students from MTsN 6 Padang City during the 2024/2025 academic year, with a sample of 266 students selected through stratified random sampling. The research instruments used were the father involvement scale and the self-control scale. Data were analyzed using descriptive statistics and Pearson Product Moment correlation. The results revealed that: (1) 34.96% of students exhibited a moderate level of self-control; (2) father involvement was also at a moderate level, with 33.08%; (3) there was a significant positive correlation between father involvement and students' self-control, with a correlation coefficient of 0.398. These findings affirm that father involvement makes a meaningful contribution to strengthening student self-control. This study has implications for family counseling services aimed at improving self-control among students with low levels of father involvement.